Ficus benjamina L. in the cities: high number of individuals, severe damages to infrastructure and expensive economic losses - Vargas-Garzón, Bellanith; Molina, Luis (UNIVERSIDAD ANTONIO NARIÑO, 2012)
The article examines the rather negative impact caused by Ficus benjamina on urban areas in tropical and subtropical zones, specifically, Colombia, Mexico and Brazil. Considered erroneously, by many as an appropriate species for urban tree planting, given its ornamental value, its low cost propagation and adaptability to urban stress, F. benjamina has been introduced massively on hot weather cities to the extent of becoming the predominant species. However, the roots of the F. benjamina have proven to be destructive of urban structures (foundations, streets, sidewalks and water systems, among others), which affect considerably the economy of the cities, yet some botanists currently conduct studies that, in fact, seek for more efficient methods of propagation of this species and promote its usage on urban settings, disregarding the widely accepted implications caused by F. benjamina and encouraging with their work a damage-repair cycle that undermine public and private financial resources in poor, developing or emerging countries.